KONTRIBUSI KOMPETENSI PEDAGOGIK DAN IKLIM ORGANISASI TERHADAP KINERJA GURU - Mulyadi, Acep (Turats, 2011)
This article will review the contribution of pedagogic competence and organizational climate on the performance of teachers. Based on the results of testing the hypothesis in this study, it can be concluded that there is a significant positive relationship between teachers' pedagogical competence in the performance of teachers of Islamic Religious Educa-tion in Elementary School at East Bekasi. There is a significant positive relationship between organizational climate with the performance of teachers of Islamic Religion Education in Elementary School at East Bekasi. There is a significant positive relationship between teacher?s pedagogical competence and organizational climate together with the performance of teachers of Islamic Religious Education in Elementary School District at East Bekasi. By looking at the above conclusion, it is known that the pedagogical competence of teachers and organizational climate contributes to a significant improvement in the performance of teachers of Islamic Religious Education in the Elementary School at East Bekasi.